3D animation as a medium of cultural representation and education : a case study of Magic Cellar part 1. - Kangong, Roland N. (My University, 2011)
Post-apartheid South African children are exposed to modern technological entertainment – television, cell phones, video games, TV animations and many other forms of popular art and media. This research report analyzes how well Magic Cellar (hereafter referred to as MC) both represents cultural diversity to a mixed audience of South African children from different ethnic backgrounds and cultures, and educates them more generally. A historical perspective on animation is provided, including animation in South Africa, as well as the technical processes of animation, and how these apply to MC. In so doing, answers to two main questions are sought: can 3D animation be used as an alternative or support to the school classroom in educating children through popular media forms? To what extent can 3D digital art technology in the form of animation be used in representing cultural diversity to children of different cultural backgrounds? Drawing on theoretical concepts, as well as comparing MC to successful programming for children that uses animation to educate, this research report argues that 3D animation, a medium that “seems to attract learners’ attention and increase their motivation to learn”(Khairezan 2), can be used to represent cultural diversity and to educate children.